Phenotypic Evaluation of a Milk Thistle Germplasm Collection: Fruit Morphology and Chemical Composition. Issue 6 (6th October 2016) - Martinelli, T.; Potenza, E.; Moschella, A.; Zaccheria, F.; Benedettelli, S.; Andrzejewska, J.
Abstract : Milk thistle [ Silybum marianum (L.) Gaertn.] is an officinal crop species native to the Mediterranean. The species is gaining increasing interest as a multipurpose crop, but lack of information exists about the natural phenotypic variability available in the species for the traits of interest. In the present work, the fruit morphological and chemical traits of a collection of 26 milk thistle accessions have been analyzed. The results show that the most variable traits are related to single flavonolignan content. When the most abundant fatty acids present in the fruit are considered, oleic acid appears to have the higher variability between accessions. Correlations between variables highlight strong relationships between the different flavonolignans and a strong positive correlation between isosilybin A and the total silymarin content, suggesting a central role of this minor flavonolignan in silymarin biosynthetic pathway. The clustering procedure displays considerable diversity between the accessions that originate from localities where milk thistle is described as a native species.